Analysis of the use bioethanol-pertalite mixtures in motorcycles on fuel consumption efficiency. Issue 1 (November 2021) - Wibowo, B S; Sari, F I P; Setiawan, Y; Prayitnoadi, P; Adha, M D
Abstract: Indonesia is one of the countries in the world that depend on fossil fuels. Fossil fuels are non-renewable fuels. The increasing use of fossil fuels causes fossil fuel reserves to dwindle, there is a need for alternative fuels. the use of alternative fuels is the right solution, alternative fuels that have been developed include bioethanol. The research method used in this study used pure pertalite data as a comparison, then continued with a mixture of bioethanol and pertalite with a variety of bioethanol and pertalite mixtures used were 10ml bioethanol 90ml pertalite, 20ml bioethanol 80ml pertalite, and 30ml bioethanol 70ml pertalite. variations of engine speed used 1000, 2000, and 3000 RPM. Then the fuel consumption data analysis was carried out on the engine. The results of the research conducted will get results for RPM 1000 with 10 ml bioethanol content, there will be less fuel consumption than pure pertalite as well as 20 ml. In the 3000 RPM Round with 10 ml bioethanol content, the fuel consumption is more efficient than pure pertalite, the same thing with bioethanol with 20 ml levels, the fuel consumption is less than pertalite.